2022
DOI: 10.1515/nanoph-2021-0667
|View full text |Cite
|
Sign up to set email alerts
|

Resonance-enhanced spectral funneling in Fabry–Perot resonators with a temporal boundary mirror

Abstract: A temporal boundary refers to a specific time at which the properties of an optical medium are abruptly changed. When light interacts with the temporal boundary, its spectral content can be redistributed due to the breaking of continuous time-translational symmetry of the medium where light resides. In this work, we use this principle to demonstrate, at terahertz (THz) frequencies, the resonance-enhanced spectral funneling of light coupled to a Fabry–Perot resonator with a temporal boundary mirror. To produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The electric tuning offers a more accessible method to control the output of the converted waves, which has significance for the application of the time-varying metasurface. In recent work, the highly efficient linear frequency conversion at the temporal boundary was experimentally demonstrated, which was attributed to the high Q factor of the resonant cavity 42 . We also found that the loss of metasurface is a crucial factor affecting the conversion efficiency (see Supplementary Notes 10 – 12 for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric tuning offers a more accessible method to control the output of the converted waves, which has significance for the application of the time-varying metasurface. In recent work, the highly efficient linear frequency conversion at the temporal boundary was experimentally demonstrated, which was attributed to the high Q factor of the resonant cavity 42 . We also found that the loss of metasurface is a crucial factor affecting the conversion efficiency (see Supplementary Notes 10 – 12 for details).…”
Section: Resultsmentioning
confidence: 99%
“…It was theoretically proposed that phase control can be used for wavefront engineering of the converted waves. In recent work, efficient frequency conversion, as well as phase coherence of the converted waves, has been observed experimentally by ultrafast modulation of structural dispersion in the waveguide 41 or loss in the Fabry–Perot cavity 42 . Despite the progress, a chip-compatible planar frequency converter with a high conversion efficiency and phase control is highly desired to advance the practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Using the exquisite design of metasurfaces, Q ‐boosting metasurfaces were proposed to break time‐bandwidth limitations and enhance the nonlinear optical responses. [ 36 ] The potential applications in photon storage [ 22 ] and spectrum compression [ 42 ] could be realized by an instantaneous change of the resonator properties. Furthermore, although our results concentrate on terahertz regime, the conclusion is universal and applicable to infrared and shorter wavelength regime.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the researches on DP are quite broad, including the dynamic evolution process of optical system [35,36] and physical system in time domain, such as synthetic dimension [37][38][39] and gauge field. [40] As for the photonic devices, DP is also widely studied in waveguide systems, [41][42][43] resonant cavity systems, [44][45][46] photonic crystal systems, [47][48][49] exciton systems. [50][51][52] Fig.…”
Section: Dynamic Photonicsmentioning
confidence: 99%